Just take the second equation and replace it for x in the first equation:
7(2y+2)-3y=3
14y+14-3y=3
11y+14=3
11y=-11
y=-1
x=2(-1)+2
x=-2+2
x=0
The solution set is (0,-1)
Check:
7(0)-3(-1)=3
3=3
0=-2+2
0=0
I hope this helps!
2007-03-10 16:12:50
·
answer #1
·
answered by Anonymous
·
4⤊
0⤋
By substituting x we get,
7 (2y+2) -3y =3
14y+14-3y=3
11y=3-14
11y =-11
y= -1
x =2y +2(given)
x =2(-1)+2
x =-2+2=0
Therefore, x=0
y= -1
2007-03-11 00:29:22
·
answer #2
·
answered by ash 2
·
1⤊
0⤋
this is how my math teacher taught it:
7x-3y=3
x=2y+2
plug in 2y+2 everywhere you see an x.
7(2y+2)-3y=3
use the distributive property
7 times 2y=14y
7 times 2=14
14y+14-3y=3
14y-3y=11y
11y-14=3
add 14 to both sides
11y=-11
divide both sides by 11
y=-1
plug in negative 1 to ONE of the first equations. i choose x=2y+2
x=2(-1)+2
2 times -1=-2
-2+2 cancel each other out
x=0
write the answer like this {0,-1}
2007-03-10 19:47:09
·
answer #3
·
answered by carrie b 2
·
1⤊
0⤋
7x-3y=3
x= 2y+2
Substitute the second equation in the first, ie
7(2y + 2) -3y = 3 ==> 14y +14 -3y = 3 ==> 11y = -11 ==> y = -1
Substitute thus value of y in the second to obtain x = 2x(-1) + 2 = 0
2007-03-10 19:12:07
·
answer #4
·
answered by physicist 4
·
1⤊
0⤋
7x - 3y = 3
x = 2y + 2
Plug the value of x from the second equation into the first.
7x - 3y = 3
7(2y + 2) - 3y = 3
14y + 14 - 3y = 3
11y = -11
y = -1
x = 2y + 2 = 2(-1) + 2 = -2 + 2 = 0
x = 0
y = -1
2007-03-10 19:09:27
·
answer #5
·
answered by Northstar 7
·
1⤊
0⤋
14y+14-3y=3
11y=-11
y=-1
x=-2+2=0
Therefore, x=0, y=-1
2007-03-10 19:24:14
·
answer #6
·
answered by JAMES 4
·
1⤊
0⤋
x=2y+2
7(2y+2)-3y=3
14y+14-3y=3
11y+14=3
11y=-11
y=-1
x=2(-1)=2
x=-2+2
x=0
(0,-1)
2007-03-10 19:07:51
·
answer #7
·
answered by o_0 2
·
1⤊
1⤋